COMPLETING APPLICATION ONLINE HIGH SCHOOL REPORT CARDS MENGGUNAKKAN MACROMEDIA DREAMWEAVER 8.0, PHP AND MYSQL - Linda Oktaviani (Jurnal Manajemen Informatika, 2010)
Website on the Internet is an effective means to convey information a product ora company with fast, accurate, and can accounted for authenticity.Filling the list of values report cards through the Internet network capable of providingease and can increase the efficiency in terms of filling a report card for teachers SMU.Untukimplementation used server side scripting programming language PHP (Personal Home Page) forinformation on the site can be accessed via the networkInternet and take advantage of theMySQL software so that the contents of the site more attractiveand dynamic.With the website is expected to homeroom teachers in partic ular to easily andefficiently in the process of filling the list of report cards to the students.